ANALISIS PERILAKU KONSUMEN DALAM MEMBELI PRODUK FASHION LOKAL DAN IMPOR DIPASAR PAGI MANGGA DUA JAKARTA UTARA - Hanisa Novelia Aambarizki Hanisa Novelia Aambarizki; Suhenda Adia Suhenda Adia; Anisa Arizona Bandi Anisa Arizona Bandi (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The purpose of this study was to analyze consumer behavior in purchasing for local and imported fashion products at F-Four Collection, Sakura Collection, and Zava Collection stores. The fashion products referred to in this study are clothing which are primary needs that must be met. Therefore humans will more often meet their primary needs. This study used data collection techniques by means of observation, interviews and written documentation, with data collection analysis, data reduction, data display, and data verification. The primary data used in this study were obtained from direct consumers, while the secondary data was from the shop owners. This study used 20 informants who were willing to conduct in- depth interviews. The results of the study indicated that consumer behavior is influenced by psychological and cultural factors which include lifestyle, economy, and a person's habits of behavior. While personal factors and social factors also influence a purchasing decision because of the encouragement or motivation from within a person that forms a person's perception of a product as well as the social and family environment that can be a determinant of a purchasing decision.